Predicting extreme anisotropy and shape variations in impact testing of tantalum single crystals. (1st April 2022) - Feng, Zhangxi; Zecevic, Miroslav; Knezevic, Marko; Lebensohn, Ricardo A.
Highlights: Crystal Plasticity captures effect of crystal orientation of Ta Taylor cylinders. Strong variations in final shapes predicted with crystal plasticity finite elements. Calibrated strain hardening and adiabatic heating constitutive laws were required. Results emphasize the need of microstructure-aware models for engineering design. Abstract: Recent Taylor cylinder impact tests carried out for Ta single crystals showed strong variations in dimensional changes for different crystallographic directions aligned with the cylindrical axis. In order to capture the effect of crystallography on the deformation characteristics and final shapes of the impacted cylinders, a single crystal material subroutine is adapted and embedded in the solid mechanics/dynamics Finite Element solver Abaqus to simulate the aforementioned single crystal Ta Taylor impact experiments. Details of the coupled model implementation, and insights on the role played by single crystal anisotropic flow on the deformation behavior across a broad range of strain rates and temperatures for different single crystal orientations are presented and discussed. We demonstrate the predictive capability of the adopted crystal plasticity model to capture the significant role played by crystal orientation-induced anisotropy, as well as strain hardening and adiabatic heating, on the dynamic deformation response of crystalline materials. This re-emphasizes the need of microstructure-aware models to improve the accuracy of simulations for high-consequence engineering design.